Health Education To Religious And Traditional Leaders Improves Knowledge, Attitude And Action In Supporting The Detection Of New Cases Of Leprosy - Saimi, Saimi; Firmansyah, Ade Surya; Suiraoka, I Putu (Politeknik Kesehatan Kemenkes Mamuju, 2024)
Background: Leprosy is still a serious health problem in Indonesia. The rate of transmission of this disease is still high, but the discovery of new cases is low and the rate of dropping out of treatment is high. This indicates that the strategies for treating leprosy that have been implemented so far have not been effective enough. So appropriate efforts are needed to overcome the problem comprehensively and sustainably. Objective: Conduct educational interventions about leprosy for religious and traditional leaders to help find cases to increase the New Case Detection Rate of leprosy. Method: Quasi-Experimental with one group pretest-posttest design. Population: are religious leaders and traditional leaders. The sample size was 50 people. Results: there was a significant increase in the variables of knowledge (p-value<0.05), positive attitudes (p-value<0.05), and actions (p-value<0.05) from religious leaders and traditional leaders regarding leprosy after the intervention. Traditional and religious leaders have a joint commitment to eradicate Hansen's Disease after intervention. Conclusion: Educational interventions for religious and traditional leaders significantly increased the knowledge, attitude and actions in supporting new case detection rate of leprosy. Recommendation: This intervention model can be followed up by relevant stakeholders to solve the problem of detecting new cases of leprosy.